The amazing Jimmi Mayes : sideman to the stars - Mayes, Jimmi, 1942-; Speek, Vickie Cleverley, 1953- (American made music series., 2014)
For more than fifty years, Chicago drummer Jimmi Mayes served as a sideman behind some of the greatest musicians and musical groups in history. He began his career playing the blues in the juke joints of Mississippi, sharpened his trade under the mentorship of drum legends Sam Lay and Fred Below in the steamy nightclubs of south Chicago, and hit it big in New York City behind such music legends as Tommy Hunt from the Flamingos, Marvin Gaye, and James Brown. Mayes played his drums behind blues giants Little Walter Jacobs, Jimmy Reed, Robert Junior Lockwood, Earl Hooker, Junior Wells, Pinet.